Analisis Waktu Pengiriman dan Harga Produk Terhadap Tingkat Penjualan di Mediasi oleh Kepercayaan - Maulana Yusup, Muhammad; Alhidayatullah, Alhidayatullah; Siwiyanti, Leonita (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2025)
This study aims to analyze the effect of delivery time and price on sales level with trust as a mediating variable among rice store consumers in Sukabumi Regency. The research applied a quantitative approach with a causal associative method. Data were collected from 112 respondents using questionnaires and analyzed using Structural Equation Modeling (SEM) with AMOS. The results revealed that delivery time positively and significantly influences both trust and sales level. Trust also has a positive and significant effect on sales level. Conversely, price does not significantly affect trust but has a negative and significant impact on sales. These findings indicate that logistical efficiency plays a more important role in building trust and increasing sales than pricing strategies. Therefore, business practitioners are advised to focus more on delivery accuracy and speed rather than merely competing on price.